Strategi Peningkatan Partisipasi Perempuan dalam Kegiatan Penyuluhan Pertanian di Subak Sembung Kota Denpasar - PRAMASANTI, NI MADE DWI SUTRA; ASTITI, NI WAYAN SRI; SARJANA, I MADE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.4, Oktober 2018, 2018)
Strategy for Increasing Women's Participation in Agricultural Extension Activities in Subak Sembung of Denpasar City The study aims to determine alternative strategies to increase women’s participation in agricultural extension activities in Subak Sembung of Denpasar City. This study aims to identify how the stengths, weakness, opportunities, and threats of increasing the participation of woman in agricultural extension activities in Subak Sembung of Denpasar City, viewed from the internal environment aspect to investigate the strengths and weaknesses, and the external aspects to find out the opportunities and threats. The research location was in Subak Sembung, Peguyangan Village of Denpasar City, Bali Province. Respondents in this study were sixty-five people. Respondents were determined by purposive sampling to investigate the internal and external environmental factors of women in Subak Sembung of Denpasar City. This study used three analyzes: internal environment analysis, external environmental analysis, and SWOT analysis (strengths, weakness, opportunities, and threats). Women’s participation in the Subak Sembung of Denpasar City has been able to utilize their stengths to overcome the weakness and participation of women in Subak Sembung is able to take advantage of opportunities to overcome the threats. There are ten alternative of strategies: SO strategy, one of which is to sell goods that are needed by the market and contain high economic value. WO strategy they continuously learn through interesting material and extension method and have big business opportunities. ST strategy, it involves women in extension activities in order to have responsibilities and to share time for family and extension activities, and WT strategy is to make more efficient and modern agricultural extension (untilizing digital media) that can be seen anytime and anywhere without disturbing other important activities.